MHC-I diversity enables rapid adaptation during a viral pandemic in wild rabbit populations - Yexin Zhang; Jonathan P. Day; Marina Lirintzi; Jiayi Ji; Clive A. Tregaskes; Miguel Carneiro; Joel M. Alves; Tanja Strive; Jim Kaufman; Francis M. Jiggins (Proceedings of the National Academy of Sciences, 2026)
Emerging diseases can have devastating consequences for wild species, with long-term effects depending on the ability of the host to evolve resistance. Here, we show that major histocompatibility complex (MHC) genes provided standing genetic variation that enabled rabbits to mount a rapid evolutionary response to the myxoma virus pandemic that began in the 1950s. Using historical and modern specimens starting in 1865 and spanning the pandemic, we found strong parallel shifts in MHC-I allele frequencies across Australia, Britain, and France, alongside population-specific signals. These evolutionary shifts are predicted to alter the peptides presented to T cells. Our results provide evidence that MHC-I is under strong selection in natural populations during a pandemic and that the high polymorphism of MHC may have contributed to the recovery of these populations.